Guest Satisfaction in Hotel Services and Guest Loyalty with Special Reference to Uttarakhand: A Study on Guest Satisfaction and Loyalty in Hospitality Sector of Uttarakhand (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The hospitality and tourism sector are one of the world's first recorded economic activity. It'slike having the comforts of home in a foreign land. The hospitality business is booming over the globe,and it is predicted to continue playing a significant role in the global economy by providing much-neededexport revenues and new job opportunities. The purpose of this research was to measure how satisfiedhotel guests were with their experiences. Both qualitative and quantitative approaches were employed togather information for this study. To ensure the study was thorough and reliable, it was necessary togather both primary and secondary data. There will be 300 people in the study's sample. The researchshows that the quality of service provided by hotels has a direct impact on customer retention andsatisfaction. The study's results will hopefully encourage hotels to prioritize guest happiness by usingmeasures like proactive customer relationship management and fine-tuning service quality.